Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1108/17542730910924745
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assessment of TQM practices: a case analysis

Abstract: PurposeThe purpose of this paper is to assess the current level of TQM practices within a major computer hard disk USA based manufacturing company in Malaysia and to identify improvement opportunities.Design/methodology/approachOriginal research using self‐administered questionnaires, distributed to all staff within this organization, is thoroughly reported. The study sample consisted of 299 employees, resulting in a response rate of 66.4 percent. The data were analyzed using descriptive and multiple regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 38 publications
4
42
0
4
Order By: Relevance
“…In other words, it could be concluded that customer orientation is positively associated with organisational performance which will potentially reap better profit for companies in the long run. Based on responses from a survey of Malaysia manufacturing companies, Arumugam et al (2009) concluded that customer orientation plays a vital role in the implementation of quality management. Based on responses from a survey of Malaysia manufacturing companies, Arumugam et al (2009) concluded that customer orientation plays a vital role in the implementation of quality management.…”
Section: The Relationship Between Customer Orientation and Business Pmentioning
confidence: 99%
“…In other words, it could be concluded that customer orientation is positively associated with organisational performance which will potentially reap better profit for companies in the long run. Based on responses from a survey of Malaysia manufacturing companies, Arumugam et al (2009) concluded that customer orientation plays a vital role in the implementation of quality management. Based on responses from a survey of Malaysia manufacturing companies, Arumugam et al (2009) concluded that customer orientation plays a vital role in the implementation of quality management.…”
Section: The Relationship Between Customer Orientation and Business Pmentioning
confidence: 99%
“…In general, these studies provide support for the hypothesis linking quality practices to quality performance. The extent review of literature further identified some common practices that are responsible to successful TQM implementation, namely: top-management commitment and leadership; strategic planning; resource management; customer focus; process management; supplier management; information and analysis; continuous improvement; teamwork; and social and environmental issues (Saraph et al, 1989;Ahire et al, 1996;Prajogo and Sohal, 2006;Ooi et al, 2010Ooi et al, , 2007aArumugam et al, 2008Arumugam et al, , 2009Teh et al, 2009a).…”
Section: Introductionmentioning
confidence: 98%
“…The word 'total' encompasses visioning and making improvement in all concerns; everything within the system and outside the system that come directly or indirectly in contact with organizational business. Proponents have presented various TQM models, however Business Excellence (BE) frameworks such as Malcolm Baldrige National Quality Award (MBNQA), European Excellence Award (EFQM model) and Australian Business Excellence Framework (ABEF) are considered the most suitable (Arumugam et al, 2009). These frameworks promote operational performance and corporate social responsibility practices with emphasis on sustainable results.…”
Section: Introductionmentioning
confidence: 99%